Patterns of cannabis use in patients with Inflammatory Bowel Disease: A population based analysis. (1st November 2015) - Weiss, Alexandra; Friedenberg, Frank
Highlights: 2084, 895 subjects with Inflammatory Bowel Disease (IBD) and 2013, 901 controls were identified from National Health and Nutrition Examination Survey (NHANES). Subjects with IBD had a higher incidence and earlier age of onset of marijuana use. Subjects with IBD were more likely to use a heavier amount of marijuana per day. IBD, male gender, age over 40 years, predicted marijuana use. Abstract: Background: Tobacco use patterns and effects in patients with Inflammatory Bowel Disease have been extensively studied, however the role and patterns of cannabis use remains poorly defined. Our aim was to evaluate patterns of marijuana use in a large population based survey. Methods: Cases were identified from the NHANES database from the National Center for Health Statistics for the time period from January, 2009 through December, 2010 as having ulcerative colitis or Crohn's disease, and exact matched with controls using the Propensity Score Module of SPSS, based on age, gender, and sample weighted using the nearest neighbor method. Results: After weighting, 2084, 895 subjects with IBD and 2013, 901 control subjects were identified with no significant differences in demographic characteristics. Subjects with IBD had a higher incidence of ever having used marijuana/hashish (M/H) (67.3% vs. 60.0%) and an earlier age of onset of M/H use (15.7 years vs. 19.6 years). Patients with IBD were less likely to have used M/H every month for a year, but more likely to use a heavier amount per day (64.9% subjects with IBD used three or more joints per day vs. 80.5% of subjects without IBD used two or fewer joints per day). In multivariable logistic regression, presence of IBD, male gender, and age over 40 years predicted M/H use. Conclusion: Our study is the first to evaluate marijuana patterns in a large-scale population based survey. Older, male IBD patients have the highest odds of marijuana use.